Sizzling Sixteen - Evanovich, Janet; King, Lorelei (New York MacMillan Audio, 2010)
Intrepid sleuth Stephanie Plum, her grandmother, and her other companions struggle to outmaneuver a killer who is targeting Vinnie, a case that is further complicated by Lula's involvement in a fraudulent investment scheme.
Unabridged.
Compact discs.
Read by Lorelei King.
Keywords: Plum, Stephanie (Fictitious character) -- Fiction; Women bounty hunters -- Fiction; Audiobooks; Trenton (N.J.) -- Fiction; Mystery fiction; Humorous fiction